2017
DOI: 10.1208/s12248-017-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Development Considerations for Nanocrystal Drug Products

Abstract: Nanocrystal technology has emerged as a valuable tool for facilitating the delivery of poorly water-soluble active pharmaceutical ingredients (APIs) and enhancing API bioavailability. To date, the US Food and Drug Administration (FDA) has received over 80 applications for drug products containing nanocrystals. These products can be delivered by different routes of administration and are used in a variety of therapeutic areas. To aid in identifying key developmental considerations for these products, a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 30 publications
1
39
0
10
Order By: Relevance
“…Following this pioneering study, many others confirmed the effectiveness of nanocrystals in improving drug bioavailability after oral administration, leading to a significant number of drug products in clinical trials or already on the market. To understand the importance of nanocrystals in the pharmaceutical field, one may note that until May 2017, the United States (US) Food and Drug Administration (FDA) has received over 80 applications for drug products containing nanocrystals, and over 60% of the submissions were for the oral route of administration [ 108 ].…”
Section: Nanocrystals (Nanosuspensions) and Bioavailabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Following this pioneering study, many others confirmed the effectiveness of nanocrystals in improving drug bioavailability after oral administration, leading to a significant number of drug products in clinical trials or already on the market. To understand the importance of nanocrystals in the pharmaceutical field, one may note that until May 2017, the United States (US) Food and Drug Administration (FDA) has received over 80 applications for drug products containing nanocrystals, and over 60% of the submissions were for the oral route of administration [ 108 ].…”
Section: Nanocrystals (Nanosuspensions) and Bioavailabilitymentioning
confidence: 99%
“…This review shows that most of the drug products are intended for an oral administration and that the pharmaceutical dosage forms are mainly tablets, capsules, or oral suspensions. In addition, one could note that the preferred technology applied is the media milling, a top-down technology that is probably better managed by the pharmaceutical industry, and that must accurately control all of the critical production factors through in-process tests and quality control end tests [ 108 ].…”
Section: Nanocrystals (Nanosuspensions) and Bioavailabilitymentioning
confidence: 99%
“…In addition, it presents greater bioadhesiveness to the biological membranes compared to the drug in the micrometric scale. Such advantages potentially improve the safety and efficacy of the drugs, allowing dose reduction (89)(90)(91)(92).…”
Section: Raman Spectroscopy In Pharmaceutical Nanomaterialsmentioning
confidence: 99%
“…In recent decades, there has been a significant rise in the development of drug nanocrystals. As of 2017, more than 80 drug nanocrystal applications were submitted to the FDA (90). The critical attribute characteristics of drug nanocrystals such as size, particle-size distribution and mean particle diameter, along with morphological analyses are fundamental to evaluate crystalline forms and to optimize size-dependent properties (90,93,94).…”
Section: Raman Spectroscopy In Pharmaceutical Nanomaterialsmentioning
confidence: 99%
“…As a result, drug absorption can be increased independent of the fed or fasting state (Müller et al, 2011). However, it is important to ensure the physical chemical properties of the drug nanocrystal during the manufacturing process and in storage throughout its shelf life (Chen et al, 2017) since these characteristics are critical for drug dissolution velocity in the nanosuspension. Kayser et al (2003) develop a nanosuspension of AMB by highpressure homogenization, using polysorbate 80 and poloxamer P188.…”
Section: Nanocrystal An Encapsulating-carrier Free Nanoparticlementioning
confidence: 99%